Examining quality time as a mediator of dyadic change in a randomized controlled trial of relationship education for low‐income couples. (29th September 2021) - Carlson, Ryan G.; Barden, Sejal M.; Locklear, Lauren; Dillman Taylor, Dalena; Carroll, Nakita
Abstract: Research identifying specific mechanisms of positive change for couples participating in relationship education is scant. Recent studies have identified the potential of communication skills as a likely mechanism, yet more information is needed about the contribution of process factors. Thus, we examined the influence that quality time spent together had on positive post‐intervention outcomes based on couples' reports of dyadic coping and dyadic adjustment for 1, 367 low‐income couples randomly assigned to receive relationship education. Results indicated that treatment couples reported significant gains in quality time spent together, and that those gains fully mediated positive changes in dyadic coping and adjustment. Additionally, actor and partner effects existed such that men's and women's reports of improved quality time influenced their own and their partners dyadic coping and dyadic adjustment. We discuss study implications for practice and future research.